Peluang Pendidikan Tinggi Bagi Pelajar Melayu Luar Bandar: Kajian Kes USM - Kassim, Mustapa (Penerbit Universiti Sains Malaysia, 1994)
This article discusses the better educational opportunity of rural Malays in higher education resulting from the implementation of the New Economic Policy (NEP) and recommendations of the Majid Report (1971). It is based on a case study of 3784 Malay graduates (1982 - 1988) in Universiti Sains Malaysia, Penang. Findings show an annual increase in the ratio of rural Malay students, especially those of lower socio-economic status and females, in the University since 1970.